2005
DOI: 10.1210/en.2005-0362
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin Inhibits Myogenesis and Promotes Adipogenesis in C3H 10T(1/2) Mesenchymal Multipotent Cells

Abstract: Inactivating mutations of the mammalian myostatin gene are associated with increased muscle mass and decreased fat mass; conversely, myostatin transgenic mice that overexpress myostatin in the skeletal muscle have decreased muscle mass and increased fat mass. We investigated the effects of recombinant myostatin protein and antimyostatin antibody on myogenic and adipogenic differentiation of mesenchymal multipotent cells. Accordingly, 10T(1/2) cells were incubated with 5'-azacytidine for 3 d to induce different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
161
3
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(180 citation statements)
references
References 44 publications
(60 reference statements)
11
161
3
5
Order By: Relevance
“…Alternatively, myostatin has been observed to promote adipogenesis in multipotential mesenchymal cells, suggesting that loss of myostatin function may directly suppress adipocyte differentiation. 9 Our results are consistent with these in vitro findings; however, it is also known that other mouse models showing increased muscle mass, such as transgenic mice overexpressing IGF-1, 10,11 Akt, 12 and ski 13 show decreased fat mass. It is therefore possible that an indirect effect of double-muscling on fat metabolism may also be involved in the resistance to body fat accumulation in the myostatin-deficient animals; however, indirect calorimetry studies have found no significant differences in the respiratory exchange ratio between normal mice and myostatin-deficient rodents.…”
Section: Discussionsupporting
confidence: 92%
“…Alternatively, myostatin has been observed to promote adipogenesis in multipotential mesenchymal cells, suggesting that loss of myostatin function may directly suppress adipocyte differentiation. 9 Our results are consistent with these in vitro findings; however, it is also known that other mouse models showing increased muscle mass, such as transgenic mice overexpressing IGF-1, 10,11 Akt, 12 and ski 13 show decreased fat mass. It is therefore possible that an indirect effect of double-muscling on fat metabolism may also be involved in the resistance to body fat accumulation in the myostatin-deficient animals; however, indirect calorimetry studies have found no significant differences in the respiratory exchange ratio between normal mice and myostatin-deficient rodents.…”
Section: Discussionsupporting
confidence: 92%
“…The use of both micro-array and proteomic analyses showed a clear fibre phenotype switch in Mst-null muscles from slow to fast-twitch fibres (Bouley et al, 2006;Steelman et al, 2006) (see section IGF-1, b 2 -agonist and myostatin-null signal fast fibre phenotype). Mst has been recently found to promote adipogenesis in C3H 10T(1/2) cells which appears to be associated with adipocyte lineage commitment (Artaza et al, 2005). However, in committed bovine preadipocytes, Mst clearly suppresses differentiation of preadipocytes into adipocytes (Hirai et al, 2007).…”
Section: Fibre Number: Mediators Of Muscle Hyperplasiamentioning
confidence: 99%
“…As an example, impairment of insulin signalling has been demonstrated in muscle cells by in vitro coculture with human adipocytes (Dietze et al, 2002). Then, the activity of adipocytes in secreting adipokines (such as leptin; Kokta et al, 2004) as well as that of muscle fibres secreting myokines (such as myostatin, Artaza et al, 2005;Hirai et al, 2007) are among the key putative mechanisms of this interaction. For instance, mutations in the myostatin gene or growth differentiation factor-8 in beef cattle increase the muscle mass in the double-muscled phenotype and leads to smaller adipocytes and fewer fat islands in muscle (Wegner et al, 1998;Cassar-Malek et al, 2007a).…”
Section: How Might Marbling Begin?mentioning
confidence: 99%